1996
DOI: 10.1152/ajprenal.1996.271.1.f198
|View full text |Cite
|
Sign up to set email alerts
|

Response of hepatic amino acid consumption to chronic metabolic acidosis

Abstract: In a previous paper, we showed that an inhibition of amino acid transport across the liver plasma membrane is responsible for the decrease in urea synthesis in acute metabolic acidosis. We have now studied the mechanism responsible for the decline in urea synthesis in chronic acidosis. Chronic metabolic acidosis and alkalosis were induced by feeding three groups of rats HCl, NH4Cl, and NaHCO3 (8 mmol/day) for 7 days. Amino acids and NH4+ were measured in portal vein, hepatic vein, and aortic plasma, and arteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
0
10
1
Order By: Relevance
“…While the directional differences observed in the ureagenic response to CMA in the humans of the present study and those reported previously in rats (6,19,23,27) remain unresolved, the degree of acidosis reported in the rat studies was modest and of lesser magnitude than that in the human data. Future studies exploring CMA in multiple species and over a range of magnitudes will be of great interest.…”
contrasting
confidence: 70%
See 2 more Smart Citations
“…While the directional differences observed in the ureagenic response to CMA in the humans of the present study and those reported previously in rats (6,19,23,27) remain unresolved, the degree of acidosis reported in the rat studies was modest and of lesser magnitude than that in the human data. Future studies exploring CMA in multiple species and over a range of magnitudes will be of great interest.…”
contrasting
confidence: 70%
“…In acute metabolic acidosis in rats induced by HCl administration, results have been modestly supportive of the hepatic regulator theory, as both decreases (3,5) and no change (8,13) in ureagenesis were reported. In chronic metabolic acidosis (CMA) in rats, however, the results have been reasonably uniform in support of the hepatic acid-base control theory inasmuch as significant reductions in urea production have been observed consistently (6,19,23,27), although one of the reports found only a transient reduction (19). Hepatic control of acid-base homeostasis may also operate in chronic metabolic alkalosis, as chronic alkali exposure in the walking catfish has been recently reported to greatly increase ureagenesis (25).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…As Mn# + can allosterically activate hepatic arginase in a pHsensitive fashion, it has been suggested that pH-dependent regulation of arginase activity may contribute to the pHdependence of hepatic urea production [211]. However, changes in hepatic amino acid transport [212,213] and possibly also in activities of key enzymes involved in amino acid catabolism, rather than changes in activities of the urea-cycle enzymes per se, are probably much more important in regulating pH-dependent alterations in hepatic urea synthesis.…”
Section: Arginase and Ureagenesismentioning
confidence: 99%
“…Furthermore, an oxidation of labeled leucine was found to correlate inversely with lipid oxidation in obese women [59]. Second, the metabolic acidosis, existing in these subjects at the fast state [23], may result in a decrease in urea synthesis due to an inhibition of amino acids transport across the liver plasma membranes as it has been shown in rats with acute HCl-induced metabolic acidosis [60].…”
Section: Discussionmentioning
confidence: 99%